Diethylaminoethylation of Chitin and the Adsorption of Acid Dyes onto the Resulting Polymer - Yoshiaki Shimizu; Tsutomu Tominaga; Yoshihiro Saito (Adsorption Science & Technology)
Water-soluble chitin derivatives have been synthesized by the diethylaminoethylation (DEAE) reaction and the adsorption characteristics of the resulting polymeric adsorbents towards two acid dyes (CI Acid Orange 7 and CI Acid Red 88) were studied. The adsorption behaviours towards these dyes were also compared with those exhibited by two water-insoluble commercially available derivatives. The conventional water-insoluble DEAE-chitins showed a high adsorptive capacity towards CI Acid Orange 7 compared to that on untreated chitin and alkali-treated chitin. A similar trend was also found for CI Acid Red 88 dye, where the increase in adsorption was characterized more clearly. However, the adsorption capacities towards both dyes exhibited by the water-soluble DEAE-chitins were increased significantly at a particular free dye concentration, with the adsorptive power also being increased both with the degree of DEAE substitution and the hydrophobicity of the dyes.